Developing Sharia Governance Index for Waqf Nazir - Muhammad Iqbal; Irfan Syauqi Beik; Indra (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2024)
One of the primary challenges facing the waqf today is the inadequate quality of nazir waqf management, characterized by a lack of accountability, transparency, and professionalism. Thus, good governance is crucial for the revival of waqf institutions, and the distinctive characteristics of the waqf institution, which originated in Islamic Sharia, clearly require governance that adheres to Sharia principles. Therefore, there is a need for a tool to evaluate and measure the implementation of Sharia governance in waqf nazir. However, there is a lack of such a tool . To fulfill that need, this study proposes the development of a Sharia Governance Index for Waqf Nazir (SGIWN). The index is developed in two steps: designing the index model and weighing the index components. The index model is developed using qualitative methods based on Islamic principles of good governance, which are verified with the help of experts in the field of waqf. Then, the AHP method is used to quantitatively determine the importance and weight of each element within the index. This study successfully develops the final composition of the index, which consists of 5 dimensions, 16 variables, and 46 indicators. This study also successfully calculates the weight of each indicator to complete the index.